Shahla Babaei Nejad, Hamideh Herizchi Ghadim, Abolfazl Ezzati, Sina Nobahari, Esmail Emami Khatib, Sima Masoudnia - Shahla Babaei Nejad; Hamideh Herizchi Ghadim; Abolfazl Ezzati; Sina Nobahari; Esmail Emami Khatib; Sima Masoudnia (Our Dermatology Online, 2015)
Introduction: Psoriasis is a chronic immune disorder that multiple factors are involved in its creation. Psoriasis is not curable but a large number of local and systemic treatments for psoriasis are available that can reduce symptoms and recurrence of the disease. Treatment is selected based on severity of illness, associated comorbidities, patient preference[including costs and convenience], and evaluation of the effectiveness of patient response to treatment. Methods: 94 cases included from patients admitted to the Sina dermatology clinic with diagnosis of psoriasis. They were randomly divided in two groups. First group treated with Calcipotriol alone while the second group treated with calcipotriol and NBUVB phototherapy. Results: According to the results of our study the subjects in the two groups in terms of sex, age, weight, height, history of systemic disease, duration of psoriasis, site of involvement and the extent of the lesions were not significantly differ. An average improvement in lesion thickness, erythema and scaling and investment, and improve overall recovery of waste per week in the fourth, eighth and twelfth week after treatment, In the second group were significantly higher than the first group. Conclusion: Daivonex cream in combination with NBUVB phototherapy has a faster and more recovery in a given time. Daivonex with NBUVB phototherapy can be used to provide better results.